Mapping the Evolution of Digital Sociology A Bibliometric Analysis of Global Research Trends (2014–2024) - Melany Pramesti; Ayu Wijayanti; Fransiskus Novrianto Pakpahan; Lesti Heriyanti (Media for Empowerment, Mobilization, and Innovation in Research & Community, 2025)
The advent of digital technologies has transformed social interactions, institutions, and research methodologies, giving rise to the field of digital sociology, which examines how digital media and big data reshape social practices and inequalities. Despite its growing influence, a comprehensive bibliometric analysis of its evolution remains scarce. This study fills this gap by systematically analyzing global research trends in digital sociology from 2014 to 2024, employing a bibliometric approach with data from Scopus and Web of Science (109 documents) and using VOSviewer for co-citation and bibliographic coupling analyses. Key findings reveal dominant themes such as algorithmic governance, digital labor, and AI ethics, with influential works by scholars like Lupton (2014), Castells (1996), and Pasquale (2015), while also highlighting gaps in digital inclusion and Global South perspectives. The study underscores the need for interdisciplinary collaboration and inclusive digital governance, providing a foundation for future research and policy decisions in addressing societal challenges posed by digital transformation.